Face aux crises : une autre Europe - Garrouste, Laurent; Mangenot, Marc; Martelli, Roger; Reungoat, Emmanuelle; Rousseau, Michel; Salesse, Yves (Paris : Syllepse, 2009)
Bibliotheek François Vercammen
Frans
Monografie